2017
DOI: 10.2319/031317-188.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maxillary central incisors on the noncleft and cleft sides in patients with unilateral cleft lip and palate—Part 1: Relationship between root length and orthodontic tooth movement

Abstract: Objectives: To measure the root lengths of maxillary central incisors (U1) and evaluate the relationship among U1 root length, tooth movement, and type of treatment appliance in patients with unilateral cleft lip and palate over a long-term follow-up period. Materials and Methods: Occlusal radiographs of 30 patients with unilateral cleft lip and palate, acquired less than 6 months before secondary alveolar bone grafting (SBG, T1) and after edgewise treatment (T2), were measured for U1 root length (R1 and R2, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There was evidence that orthodontic tooth movement stimulates bone apposition, it was not necessary for the bone thickness to be at least the root width of the adjacent teeth [ 38 ], and bone resorption in the most inferior 1/4 level was acceptable [ 20 ]. Furthermore, in 5 patients, it was found that root length of the central incisor at the cleft side was less than 9 mm due to higher probability of malformation [ 39 ], thus bone bridge assessment at the level of 9 mm was compared with the root diameter measured 0.5 mm beneath the apex, though the scores at this level were all above 2, but they might face higher risk of root resorption in the orthodontic treatment after SABG procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence that orthodontic tooth movement stimulates bone apposition, it was not necessary for the bone thickness to be at least the root width of the adjacent teeth [ 38 ], and bone resorption in the most inferior 1/4 level was acceptable [ 20 ]. Furthermore, in 5 patients, it was found that root length of the central incisor at the cleft side was less than 9 mm due to higher probability of malformation [ 39 ], thus bone bridge assessment at the level of 9 mm was compared with the root diameter measured 0.5 mm beneath the apex, though the scores at this level were all above 2, but they might face higher risk of root resorption in the orthodontic treatment after SABG procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, patients need orthodontic treatment before and after cleft repair surgery. Inappropriate forces to incisors may have negative effect on root length and ABS of tooth (Maeda et al, 2017; Yatabe et al, 2015). So they should be taken into consideration when treatment starts.…”
Section: Discussionmentioning
confidence: 99%
“…Maeda-lino found that the root lengths of U1 were comparatively short on the cleft side in patients with UCLP treated with MPA before SABG. Thus, they concluded that orthodontic force exerted by the MPA before SABG might result in short dental roots [58].…”
Section: Management Of Maxillary Deficiency In Growing Cleft Patientsmentioning
confidence: 99%